The Effect of ESG Performance and Cost of Debt on the Credit Ratings of Companies Listed on the Indonesian Stock Exchange - Ahmad Nur Ardiansyah; Sriwati (Devotion : Journal of Research and Community Service, 2026)
This study aimed to examine the effects of Environmental, Social, and Governance (ESG) performance and cost of debt on the credit ratings of cross-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Using a purposive sampling method, a sample of 19 companies was selected, resulting in 57 panel data observations. The data were analyzed using ordinal logistic regression with a complementary log-log link function, incorporating leverage, firm size, and profitability (Return on Assets or ROA) as control variables. The empirical results showed that ESG performance and firm size had positive and significant effects on the probability of achieving higher credit ratings, providing theoretical support for the application of Signalling Theory and Legitimacy Theory. Conversely, cost of debt, leverage, and profitability did not have significant effects on credit ratings. These findings indicated that independent rating agencies consider sustainability transparency as an important signal for mitigating fundamental risks, whereas debt costs are perceived primarily as operational consequences that do not directly alter the hierarchy of creditworthiness assessments.